Farnesylamine from the Ant Monomorium fieldi Forel - Jones, T.; Clark, D.; Heterick, Brian E.; Snelling, R. (American Chemical Society and American Society of Pharmacognosy, 2003)
(2E)- and (2Z)-Farnesylamine were detected in the extracts of the myrmicine ant Monomorium fieldi Forel from Australia. Their structures were established by direct comparison with synthetic (2E)- and (2Z)-farnesylamine. This finding of a sesquiterpene is unique in a genus known to produce unbranched fatty acid derived alkaloids and amines. Additionally, while farnesylamine has not been reported from natural sources, the synthetic material has been shown to have a variety of biological activities.